2021
DOI: 10.1007/s00256-021-03790-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI after Whoops procedure: diagnostic value for residual sarcoma and predictive value for an incomplete second resection

Abstract: Objective To determine the value of MRI for the detection and assessment of the anatomic extent of residual sarcoma after a Whoops procedure (unplanned sarcoma resection) and its utility for the prediction of an incomplete second resection. Materials and methods This study included consecutive patients who underwent a Whoops procedure, successively followed by gadolinium chelate-enhanced MRI and second surgery at a tertiary care sarcoma center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…There was patient spectrum bias in four studies, because these studies also included some patients who underwent neoadjuvant therapy before re-excision [13,14] and some patients with other soft tissue malignancies than sarcoma [4,17]. In addition, in 4 of the included studies [12,14,16,17], MRI was reviewed by consensus of two interpreters, which does not mirror the independent readings that radiologists typically perform in clinical practice. Interobserver agreement for residual tumor at MRI was reported by only one study and was reported to be perfect (κ value of 1.00) [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There was patient spectrum bias in four studies, because these studies also included some patients who underwent neoadjuvant therapy before re-excision [13,14] and some patients with other soft tissue malignancies than sarcoma [4,17]. In addition, in 4 of the included studies [12,14,16,17], MRI was reviewed by consensus of two interpreters, which does not mirror the independent readings that radiologists typically perform in clinical practice. Interobserver agreement for residual tumor at MRI was reported by only one study and was reported to be perfect (κ value of 1.00) [2].…”
Section: Discussionmentioning
confidence: 99%
“…This remains a topic for future study. Specificity of MRI was fairly high but not perfect, which may be explained by the presence of postoperative hematoma, granulation tissue or scarring which could in some cases be mistaken for residual soft tissue sarcoma [12,17,16,24]. Specificity may be improved by using image subtraction in gadolinium-enhanced MRI [12], diffusionweighted (DW) MRI, and/or dynamic contrast-enhanced (DCE) MRI [16,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations